2020
DOI: 10.1167/tvst.9.10.33
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Lifetime Imaging Ophthalmoscopy (FLIO) in Patients with Choroideremia

Abstract: To provide a detailed characterization of choroideremia (CHM) using fluorescence lifetime imaging ophthalmoscopy (FLIO) and to provide a deeper understanding of disease-related changes and progression. Methods: Twenty-eight eyes of 14 patients with genetically confirmed CHM (mean age, 28 ± 14 years) and 14 age-matched healthy subjects were investigated in this study. FLIO images of a 30°retinal field were collected at the Moran Eye Center using a Heidelberg Engineering FLIO device. FLIO lifetimes were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Two previous FLIO studies investigated patients with choroideremia. 47 , 50 In one study, the authors argued that the short FLIO lifetimes may originate from an accumulation of the visual cycle byproduct all- trans retinal, which typically shows short fluorescence lifetimes. 51 According to the authors, this could indicate preserved metabolic activity in the photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous FLIO studies investigated patients with choroideremia. 47 , 50 In one study, the authors argued that the short FLIO lifetimes may originate from an accumulation of the visual cycle byproduct all- trans retinal, which typically shows short fluorescence lifetimes. 51 According to the authors, this could indicate preserved metabolic activity in the photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 A second FLIO study on patients with choroideremia found short FLIO lifetimes originating from areas with outer retinal tubulations. 50 Short FLIO lifetimes within atrophic retinal areas may indicate areas of at least partially preserved photoreceptor structure, which eventually might indicate preserved photoreceptor function. This might be an interesting finding to consider when identifying patients who might benefit from enrollment in early clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of hydroxychloroquine toxicity, where early toxicity detection is challenging, FLIO could provide a better alternative to electroretinogram (ERG) or OCT, since it can detect prolonged FLTs before structural changes appear (465,466). FLIO has also been used to identify changes in other retinal conditions as well, including DR (Figure 7), vascular occlusive diseases, CSR, choroideremia, RP, and macular holes, and is believed to be a promising diagnostic method (463,(467)(468)(469)(470)(471)(472)(473).…”
Section: Fluorescence Lifetime Imaging Ophthalmoscopymentioning
confidence: 99%
“…show that FLIO can detect an increase in autofluorescence lifetime in the diseased tissue of a small cohort of patients with choroideremia, an ocular disease, compared to normal surrounding tissue 30 [Fig. 3(a), middle panel].…”
Section: Autofluorescence Flim Applicationsmentioning
confidence: 99%